Causal association between adiponectin and the risk of Alzheimer's disease: A Mendelian randomization study - Jin, Tianyu; Huang, Wei; Cao, Fangzheng; Yu, Xinyue; Ying, Zhenhua; Guo, Shunyuan; Cheng, Yifan; Xu, Chao (Frontiers in Neurology, 2022)
Background Numerous observational studies have revealed that circulating adiponectin (ADPN) is associated with Alzheimer's disease (AD) risk. However, the causality remains unknown. We aimed to assess the causality of circulating ADPN on AD risk using Mendelian randomization (MR). Methods Fourteen single nucleotide polymorphisms (SNPs) significantly associated with ADPN were selected from publicly available genetic abstract data. We applied these SNPs to two recent large-scale genome-wide association studies (GWAS) of AD, one from the FinnGen consortium and the other from a large meta-analysis. The inverse variance weighted method, MR–Egger method, the weighted median method, the Cochran Q statistic, the MR-Pleiotropy Residual Sum and Outlier methods, and the leave-one-out analysis were applied for MR analyses. Results In MR analysis, no significant genetic association was found between plasma ADPN levels and AD risk by analyzing the FinnGen consortium GWAS database in the inverse variance weighted method [odds ratio (OR): 0.874, 95% confidence interval (CI): 0.701–1.089, p = 0.230], MR–Egger (OR: 0.944, 95% CI: 0.692–1.288, p = 0.721), and weighted median method (OR: 0.900, 95% CI: 0.678–1.194, p = 0.449). Additionally, the same analysis was conducted for the meta-analysis database, and we found no significant association (OR: 1.000, 95% CI: 0.999–1.001, p = 0.683). Conclusion Our findings reveal no significant causal association between circulating ADPN and AD risk.